2020
DOI: 10.1108/jima-05-2019-0109
|View full text |Cite
|
Sign up to set email alerts
|

Does country governance and bank productivity Nexus matters?

Abstract: Purpose This study aims to examine the impact of country governance and other potential bank-specific characteristics and macroeconomic condition determinants on bank productivity in the period of 2006–2016. Design/methodology/approach The productivity level of total 167 banks selected from Malaysia, Indonesia, Brunei and Singapore are evaluated using the data envelopment analysis-based Malmquist productivity index method. A panel regression analysis framework based on ordinary least squares, a fixed effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…They found a positive link between the previously mentioned governance indicators and bank efficiency (more efficient banks are expected to lend more). The findings further supported Kamarudin et al (2020) and Athari and Bahreini (2021), who found that enhanced RQ boosted bank performance. Lensink et al (2008) found that improved RL promoted credit growth, as did higher CC (Chortareas et al , 2012).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…They found a positive link between the previously mentioned governance indicators and bank efficiency (more efficient banks are expected to lend more). The findings further supported Kamarudin et al (2020) and Athari and Bahreini (2021), who found that enhanced RQ boosted bank performance. Lensink et al (2008) found that improved RL promoted credit growth, as did higher CC (Chortareas et al , 2012).…”
Section: Resultssupporting
confidence: 83%
“…The number of studies using six QoG indicators has been limited. It has been indicated that QoG received very little attention during the [2007][2008] Trust and country governance GFC (Kamarudin et al, 2016(Kamarudin et al, , 2020. Other studies have used the average of the six QoG with the financing margins of Islamic banks.…”
Section: Imefm 163mentioning
confidence: 99%
“…The results are then tested using a parametric (t test) and nonparametric (Mann-Whitney [Wilcoxon] and Kruskal-Wallis) test in order to determine the variances in the productivity (y-axis) of Islamic and conventional banks. This test is widely used in prior banking productivity studies [14,37]. Table 4 presents the summary statistics of data used to construct the productivity frontiers for Islamic and conventional banks.…”
Section: Resultsmentioning
confidence: 99%
“…This paper examines its relationship between EM and efficiency in the frontier market banking sector from 2011 - 2018. The objective is to determine whether EM adversely impacts efficiency, for a decline in efficiency will stifle a firm's growth and erode the firm's competitiveness ( Kamarudin et al, 2020 ). EM's association with efficiency is particularly important in a market where banks predominately fill funding gaps ( Vo, 2020 ), and the lack of funding can impede development and expansion ( López Salazar et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%